2019
DOI: 10.24843/eja.2019.v29.i02.p17
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Rasio Keuangan Perbankan Terhadap Profitabilitas

Abstract: ABSTRAKPenelitian ini dilakukan untuk menguji pengaruh variable bank Size, LDR, NPL, BOPO, NIM, terhadap ROA pada industri perbankan pembangunan daerah di Indonesia. Metode dalam pengumpulan data, penjelasan mengenai definisi opersional variabel, dan penjelasam teknis analisis yang akan dilakukan menggunakan metode kuantitatif. Hasil penelitian ini mendukung Teori Bank Loan Rate Mark Up dimana LDR, NPL dan NIM berpengaruh terhadap ROA, dengan keuntungan bunga yang meningkat mampu meningkatkan ROA. ABSTRACTThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 9 publications
3
12
0
8
Order By: Relevance
“…A positive relationship means if the NIM value increases, it increases ROA and vice versa. This result is in line with research from Setiawan (2017), Susanto and Kholis (2016), Manikan and Syafruddin (2013), and Kurniasih (2016). Therefore, the H4 of this study is accepted.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…A positive relationship means if the NIM value increases, it increases ROA and vice versa. This result is in line with research from Setiawan (2017), Susanto and Kholis (2016), Manikan and Syafruddin (2013), and Kurniasih (2016). Therefore, the H4 of this study is accepted.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 91%
“…The result of Septiani and Lestari (2016), Agustami (2011), Setiawan (2017), Susanto and Kholis (2016), Manikan and Syafruddin 2013, and Kurniasih (2016) stated that NPL has negative effect to profitability. In the other hand, Harun (2016) stated that NPL has positive effect to profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the statistical t test showed that the CAR variable (X1) had a non-significant negative effect on ROA, This study is in line with the results of research on Heri Susanto and Nur Kholis [1], Mario Christiano, Parengkuan Tommy and Ivonne Saerang [2], showing that CAR (Capital Adequacy Ratio) has a significant effect on ROA (Return On Asset). ROA = α + X1 + X2 + X3 + X4 + e ROA = -0,645 -0,033 X1 + 0,017 X2 + -0,090 X3 + 0,164 X4 + e B.…”
Section: A Effect Of Car On Roasupporting
confidence: 86%
“…Seen from the F test results shown in the ANOVA table, it can be found that together, the CAR, LDR, NPL and NIM variables influence ROA, This is in line with the results of research on Heri Susanto and Nur Kholis [1], Mario Christiano, Parengkuan Tommy and Ivonne Saerang [2], showing that CAR, LDR, NPL and NIM simultaneously have a significant influence on ROA. Based on this research, it shows that the CAR, LDR, NPL and NIM variables influence ROA, because it indicates that the smaller the CAR, LDR, NPL and NIM, the smaller the value of ROA or the greater the CAR, LDR, NPL and NIM, the greater the value ROA V. CONCLUSION Based on the results and discussion, it can be concluded that CAR has no significant negative effect, while LDR has no significant positive effect on ROA.…”
Section: E Effect Of Car Ldr Npl and Nim On Roasupporting
confidence: 82%
“…Menurut Susanto & Kholis (2016) Cash Ratio merupakan likuiditas minimum yang harus dipelihara oleh bank dalam membayar kembali pinjaman jangka pendek bank. Sedangkan menurut Ramadaniar, Dkk (2013) Quick Ratio adalah rasio yang dipergunakan mengukur kemampuan bank dalam memenuhi kewajibannya terhadap para deposan.…”
Section: Pendahuluanunclassified